Equine-assisted activities and therapies for children with autism spectrum disorders - Peters, B. Caitlin, author; Wood, Wendy, advisor; Bundy, Anita, committee member; Hepburn, Susan, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2018)
Objective: The purpose of this dissertation is to systematically map, and then advance, the state of scientific and theoretical development of equine-assisted activities and therapies (EAATs) for children with autism spectrum disorders (ASD). Method: This dissertation is composed of two studies. The first study was a systematic mapping review of peer-reviewed literature relevant to EAATs for children with ASD. In conjunction with my research team, I gathered peer-reviewed literature pertaining to EAATs for children with ASD, and extracted information from each paper about scientific methods, participants, interventions, theory, and outcomes. Guided by the results of the first study, the second study was a mixed-method investigation of occupational therapy in an equine environment (OTee). The quantitative strand consisted of a multiple-baseline single-case experimental design, investigating the efficacy of OTee on occupational performance, behavior, and social functioning of eight children with ASD. The qualitative strand adopted a generic qualitative research approach; I conducted interviews with two occupational therapists, aimed at elucidating the theoretical rationale guiding OTee for children with ASD. Results: In the systematic mapping review, five types of equine-assisted activities were identified across 25 studies, with reported improvements in behavior, social interaction, and communication. Four types of equine-assisted therapies were identified across eight studies, with reported improvements in motor control and self-care. Different approaches to therapeutic riding and hippotherapy, the most studied interventions, were evident. Theoretical linkages among change mechanisms, intervention designs incorporating horses, and outcomes were rare. Explanatory formal theories and possible change mechanisms were more prevalent. Guided by findings, we propose that a) equine movement, manipulated by a therapist, challenges and improves postural control, and that an equine-assisted activity or therapy can, b) promote engagement, a platform for social development, and c) provide structured support for social interaction and positively reinforce communication. While promising, these three nascent theoretical frameworks merit further critique, testing and refinement. In study 2, children with ASD who received 10 weeks of OTee demonstrated improvements in individualized occupational performance goals, social communication, and social motivation. Some, but not all, participants also demonstrated a decrease in hyperactive and irritable behaviors. Children did not demonstrate significant changes in social cognition, social awareness, or restricted and repetitive behaviors. Occupational therapists portrayed OTee as a holistic intervention that provides children with opportunities to learn and practice a variety of skills within a motivating context where children are purposefully engaged in equine-related occupations. Derived from interview data, a concept map of therapists' clinical reasoning delineates hypothesized mechanisms of change, including the role of the horse, that lead to improvements in the following outcomes: a) cognitive skills, b) motor skills, c) attention and engagement during therapy, d) social interaction, e) communication, f) behavior, and g) safety. Qualitative results elucidated specific mechanisms and intervention components that may have led to improved occupational performance, behavior, and social functioning in the quantitative strand. Conclusion: Peer-reviewed literature pertaining to EAATs for children with ASD is in early stages of scientific and theoretical development. Promising outcomes support continued investigation focused on conceptual development and testing of theoretical frameworks, standardization, appropriateness, and efficacy. One type of EAAT, OTee, is a highly individualized intervention that requires clinical reasoning to incorporate the unique affordances of the equine environment into individualized occupational therapy; when tailored to the individual needs of children with ASD, OTee may improve occupational performance, hyperactivity, irritability, social communication, and social motivation.
Keywords: equine-assisted activities and therapies; mixed methods; therapeutic riding; hippotherapy; autism; review